(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
Generally, synchronous generators permanent magnet model (PMSG) are often used in wind energy conversion systems applications (low to medium power). The PMSG control used in mentoring and induction machine applications has many similarities. Can be controlled in nested speed-torque loops of the synchronous machine via a power electronics converter-specific application. Due to the nonlinearity systems of the wind energy conversion systems (WECS), can be used the feedback linearization control FLC to find the optimal solution in the present paper. To adapt this approach in WECS has been applied to energy conversion systems based on grid-synchronous generators.